THE INVESTIGATION OF WEAR MECHANISM ON HEAVY EQUIPMENT UNDERCARRIAGE COMPONENT (BUSHING) AND THE EFFECT OF SOIL TYPES TO WEAR OF SUCH COMPONENT - EKO SULISTIAWAN, SURYA
Wear is one of the most common problems in various heavy equipment components. One manufacturer of heavy equipment had one case related to wear problem. Wear occured at bushing, the undercarriage component in heavy equipment that act as connector between chains. The wear phenomenon was claimed by the manufacturer had a high wear rate and in general the wear rate of bushing is different at each location of the heavy equipment was operating. Claims by manufacturer about the phenomenon of wear is precisely the case behind the purpose of the research. The objective of this research is to know wear mechanism on bushing through the observation of worn components and to determine the relation between soil types to bushing wear level through wear resistance test which refer to ASTM B611 standard. The observation of worn components was done using visual, chemical composition checking, microstructure observation, measurement of each phase thickness, hardness test, and SEM observation. While the wear resistance test was carried out using a tool developed in this study that reference to ASTM B611 standard. The wear mechanism at bushing begins with contact and friction between bushing, sprocket, and soil. The contact and friction generate shear stress and compression stress that occurs in the bushing. Due to the shear stress exceeding the shear strength, the bushing surface undergoes plastic deformation. Plastic deformation occurs both in the pearlite ferrite phase and tempered martensite phase. Furthermore, the surface of the bushing is worn out and a new contact surface will begin to contact and rub back again. Constant compression load, but the thinning contact surface and brittle lead to initiation of cracks and then followed by the propagation of crack. Based on the results of the wear resistance test, the total mass reduction of specimens with soil types variation from highest to lowest is plastic soil (75% silica), plastic soil (60% silica), non-plastic soil (80% silica), and non-plastic soil (70% silica). With the variation of friction speed, in the non-plastic soil the higher speed then the mass reduction of specimens is greater, but in the plastic soil there is not seen any trend of the influence of speed variation. In addition, mass reduction trend of specimens in non-plastic soil tend to linear over time while the plastic soil has a different trend.